Geometric aspects of analysis and mechanics in honor of the 65th birthday of Hans Duistermaat - Ban, Erik P. van den; Kolk, Johan A. C. 1947- (Progress in mathematics, 2011)
Hans Duistermaat, an influential geometer-analyst, made substantial contributions to the theory of ordinary and partial differential equations, symplectic, differential, and algebraic geometry, minimal surfaces, semisimple Lie groups, mechanics, mathematical physics, and related fields. Written in his honor, the invited and refereed articles in this volume contain important new results as well as surveys in some of these areas, clearly demonstrating the impact of Duistermaat's research and, in addition, exhibiting interrelationships among many of the topics.